THE REPEAL OF INDONESIA’S DEATH PENALTY FOR CORRUPT OFFICIALS - Dwi Seno Wijanarko (Adisam Publisher, 2026)
The implementation of the death penalty for corruptors in Indonesia is criticized for its ineffectiveness in deterring corruption and its inconsistency with the country’s commitment to upholding human rights. While some nations enforce the death penalty for corruption with minimal success, others achieve better results through preventive measures that do not involve capital punishment. The death penalty is seen as contradicting Indonesia's legal framework and international human rights obligations, as it is equated to state-sponsored premeditated murder. As an alternative, this paper proposes impoverishing corruptors by recovering misappropriated state assets and imposing restrictions on their civil and political rights, thereby preventing recidivism and reducing future harm to the state. This approach would align with human rights principles while fostering a more effective anti-corruption strategy.